Rekayasa Akrual untuk Meminimalkan Pajak - Lilis Setyowati (The Indonesian Journal of Accounting Research, 2013)
Accounting give managers a flexibility in choosing methods and many making estimation as long as the discretionary is based on rational and logic judgment. One of many incentives that were proved by many researches could influence managers discretionary was tax saving.on September 1994, it was announced that tax income would be reduced. This regulation was effective at January 1st, 1995. Tax reducing can be seen by managers as an opportunity to minimze tax. Manager can shift income from this period to the next period with lower tax income. Income shifting can be done by accelerating revenues recognition or deferring expenses recognition through many methods. Using 48 manufacture companies that are going public at Jakarta Stock Exchange, it could not be found that there were opportunistic motive behind financial statements preparations. This research only gave weak evidence about earnings management as an incentive to make tax saving.